2014
DOI: 10.1158/2159-8290.cd-13-0945
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transition Activates PERK–eIF2α and Sensitizes Cells to Endoplasmic Reticulum Stress

Abstract: Epithelial-to-mesenchymal transition (EMT) promotes both tumor progression and drug resistance, yet few vulnerabilities of this state have been identifi ed. Using selective small molecules as cellular probes, we show that induction of EMT greatly sensitizes cells to agents that perturb endoplasmic reticulum (ER) function. This sensitivity to ER perturbations is caused by the synthesis and secretion of large quantities of extracellular matrix (ECM) proteins by EMT cells. Consistent with their increased secretor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
237
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(264 citation statements)
references
References 50 publications
(40 reference statements)
17
237
2
2
Order By: Relevance
“…We found that NACA deficiency does trigger the UPR in zebrafish larvae, and that treatment of naca mutants with the chemical chaperon 4-PBA significantly suppressed SRC apoptosis, and restored CHT haematopoiesis. Interestingly, EMT-derived mesenchymal cells in general were recently shown to be exquisitely sensitive to ER stress-induced apoptosis 30 . This feature was shown to be linked to their high level of extracellular matrix secretory activity, which involves steady ER development.…”
Section: Discussionmentioning
confidence: 99%
“…We found that NACA deficiency does trigger the UPR in zebrafish larvae, and that treatment of naca mutants with the chemical chaperon 4-PBA significantly suppressed SRC apoptosis, and restored CHT haematopoiesis. Interestingly, EMT-derived mesenchymal cells in general were recently shown to be exquisitely sensitive to ER stress-induced apoptosis 30 . This feature was shown to be linked to their high level of extracellular matrix secretory activity, which involves steady ER development.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and 3D hydrogel studies were performed as previously described (18,28). All computational analyses, reagents, public datasets used, and other protocols are described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…This molecule induces cell death in a CHOP-dependent manner in a number of cell lines, and there is enthusiastic support to develop this molecule for cancer therapy. A recent study also suggests that modulation of ER stress could be a selective target for cancer cells that undergo EMT (Feng et al 2014). During EMT, cells secrete more secretory molecules, such as extracellular matrix proteins, which provokes eIF2α phosphorylation and subsequent ATF4 induction.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Thus, cells undergoing EMT are more sensitive to ER stress compared with cells without EMT. This selective toxicity of cells stressed by a harsh environment or protein misfolding offers a selective advantage to using these agents to uniquely destroy tumor cells (Feng et al 2014).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%